2019
DOI: 10.11596/asiajot.15.69
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Adjustability of Grasping Force between Young People and Elderly Individuals

Abstract: This study aimed to compare adjustability of grasping force (AGF) between people belonging to young and elderly age-groups. Methods: Twenty young people and 20 elderly people, with no previous pathology involving the hands and fingers, were included in the study, and an AGF assessment was performed for all the subjects using an iWakka. Subjects adjusted the grasping force according to the target value displayed on the monitor by opening or closing the iWakka. Results: The assessment of AGF was performed separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Finally, Kaneno et al 2 reported that the older adult had lower AGF than younger individuals in situations in which concurrent visual feedback was used, as in the acquisition phase of this study. The authors state the need for an intervention regarding this ability.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Finally, Kaneno et al 2 reported that the older adult had lower AGF than younger individuals in situations in which concurrent visual feedback was used, as in the acquisition phase of this study. The authors state the need for an intervention regarding this ability.…”
Section: Discussionmentioning
confidence: 64%
“…Older adults have been reported to perform worse than younger people in AGF tasks using visual information 2 , 3 . However, the effect of the ability to properly adjust the grasping force without relying on external information and the speed to reflect visual information in movement has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). A previous study involving healthy older adults reported that the AGF differed depending on each section, requiring different adjustment methods for each interval [15]. Therefore, this study aimed to obtain insights into the task characteristics of adjustment by calculating the AGF (g) for the total sections and each section individually.…”
Section: Agfmentioning
confidence: 99%